Influence of earth gravity on reaction engineering of tubular reactor for high concentration tungsten ion-exchange - 赵中伟 肖露萍 郭持皓 陈星宇 陈爱良 霍广生 李洪桂 (Transactions of Nonferrous Metals Society of China, 2010)
The influence of gravity on the reaction engineering of tubular reactor is studied by analyzing the residence time distribution curves.The results show that upflow-feeding mode is more beneficial compared with downflow-feeding mode,since the flow pattern of the fluid in the reactor is closer to plug flow.The result of dynamic experiment conducted in ion-exchange of tungsten metallurgy is as good as that in reaction engineering of ion-exchange column.Whether downflow-feeding or upflow-feeding mode is adopted,breakthrough time decreases when solution concentration increases.Upflow-feeding mode has longer breakthrough time and greater improvement in adsorption capacity especially with high WO3 concentration in ion-exchange.